(untitled) (Asian Education Studies, 2021)
At present, students major in photo electricity information science and engineering, measurement and control technology and instrumentation of colleges and universities are not interested in the compulsory courses which require higher theoretical basis. And teaching efficiency of such courses is bad. Aiming at the issue, we put forward some important measures on how to motivate students‟ interest and improve the teaching efficiency of compulsory courses of such majors with a combination of course: Laser Principle and Application. From the aspect of teachers, a teacher shall accumulate rich application examples in various fields and prepare lessons efficiently. It is a precondition for improving compulsory course teaching efficiency. It is also effective guarantee to carry out vivid classroom teaching with a combination of cutting-edge technological development. Besides, it is fundamental guarantee for a teacher to bring in diversification means in the big data era and adopt advanced teaching methods. From the aspect of students, rich learning interest and positive learning attitude are the fundamental power to improve compulsory course teaching efficiency. In addition, necessary engineering practice ability cultivation is the fundamental goal.